Екологічна безпека промислових об’єктів - Куренков, В. С. (ХНУРЕ, 2022)
This work is devoted to the environmental safety of industrial facilities, or more precisely, the correct definition of the concept of environmental safety and the development of an approach to achieve it. This topic is particularly relevant in our country, as the basis of our economy is industry. Unfortunately, at the present moment there are only some scattered recommendations, and not an exact system of instructions, using which the heads of industrial facilities could guarantee the safety of the environment. To solve the above-mentioned problem I propose to form such a system.
Keywords: environmental safety; industrial facilities